Addressing the biblical and ecclesial obligation of Nigerian Roman-Catholic priests in promotion of peace and social justice - Ezeanya, Oguejiofo C. P. (HTS teologiese studies, 2021)
Some of the Nigerian Roman-Catholic priests had been murdered by armed criminals in the presbyteries on account of their witnessing to the gospel truth. Others have continued to receive threats of molestation and death for the same reason. This necessitated the current study that adopted an etymological approach and secondary sources of data, such as journal articles, newspaper publications and policy briefs, to discuss on how to address the biblical and ecclesial obligation of Nigerian Roman-Catholic priests in promotion of peace and social justice.Contribution: The article provides that the target of the Nigerian Roman-Catholic priests was not just to console the dejected of the society over the neglect of the leaders but include the thrust of actions that would get both the leaders in the government and the populace to know their respective duties and be compelled to do them.